Toxoplasma gondii decreases the reproductive fitness in mice - Dvorakova-Hortova, Katerina; Sidlova, Adela; Ded, Lukas; Hladovcova, Denisa; Vieweg, Markus; Weidner, Wolfgang; Steger, Klaus; Stopka, Pavel; Paradowska-Dogan, Agnieszka (PloS one, 2014)
Toxoplasma gondii is a common protozoan parasite that infects warm-blooded animals throughout the world, including mice and humans. During infection, both, the parasite and the host, utilize various mechanisms to maximize their own reproductive success. Mice and humans are both the intermediate hosts for Toxoplasma gondii, which forms specialized vacuoles containing reproductive cysts in the formers' tissue. As half of the human population is infected, developing a disease called toxoplasmosis, along with an ever-growing number of couples suffering with idiopathic infertility, it is therefore surprising that there is a lack of research on how Toxoplasma gondii can alter reproductive parameters. In this study, a detailed histometric screening of the testicular function along with the levels of the pituitary luteinizing hormone (LH) were analysed in infected mice. Data on relative testis and epididymis weight, and sperm count were also collected. Based on the results obtained, the level of LH in the urine of Toxoplasma gondii infected mice was lower compared to the control. In direct correlation with the hormone level, testicular function and sperm production was also significantly lower in Toxoplasma gondii positive group using sperm count and histometric analysis as a marker. Not only were the number of leptotene primary spermatocytes and spermatids lowered, but the number of Sertoli cells and the tubule diameter were elevated. In parallel, a pilot epigenetic study on global testicular methylation, and specific methylation of Crem, Creb1 and Hspa1genes essential for successfully ongoing spermatogenesis was performed. Global methylation was elevated in Toxoplasma infected mice, and differences in the DNA methylation of selected genes were detected between the Toxoplasma positive and control group. These findings demonstrate a direct relation between Toxoplasma gondii infection and the decrease of male reproductive fitness in mice, which may contribute to an increase of idiopathic infertility in humans.
Keywords: spermie; epididymis; epigeneze genetická; toxoplazmóza zvířat; Cyclic AMP Response Element-Binding Protein; Luteinizing Hormone; Epididymis; Male; Oligospermia; semenotvorné kanálky; Epigenesis, Genetic; CpG Islands; Toxoplasmosis, Animal; myši inbrední C57BL; HSP70 Heat-Shock Proteins; mužské pohlaví; oligospermie; Sertoliho buňky; Mice; CpG ostrůvky; modulátor elementu responzivního pro cyklický AMP; Seminiferous Tubules; luteinizační hormon; Sertoli Cells; Gene Expression; zvířata; Humans; metylace DNA; Toxoplasma; Host-Parasite Interactions; genetická zdatnost; Cyclic AMP Response Element Modulator; DNA Methylation; protein vázající cAMP responzivní element; interakce hostitele a parazita; myši; exprese genu; Spermatozoa; proteiny tepelného šoku HSP70; Mice, Inbred C57BL; lidé; Genetic Fitness; Animals